Targeting stroke risk and improving outcomes in patients with atrial fibrillation in Latin America - Stambler, Bruce (2016)
CONTEXT AND OBJECTIVE: To examine stroke risk factors, including atrial fibrillation, management and prevention, and stroke outcomes across Latin America. DESIGN AND SETTING: Narrative review conducted at Piedmont Heart Institute, United States. METHODS: The PubMed, Embase and Cochrane databases were searched for stroke AND “Latin America” AND epidemiology (between January 2009 and March 2015). Further studies in the SciELO, World Health Organization and Pan-American Health Organization databases were used to address specific points. RESULTS: Countries categorized as low or middle-income nations by the World Bank, which includes most of Latin America, account for two-thirds of all strokes. Globally, fewer than half of patients (median treatment level: 43.9%) with atrial fibrillation receive adequate anticoagulation to reduce stroke risk, which correlates with data from Latin America, where 46% of outpatients did not receive guideline-compliant anticoagulation, ranging from 41.8% in Brazil to 54.8% in Colombia. CONCLUSIONS: Atrial fibrillation-related stroke carries a heavy burden. Non-vitamin K antagonist oral anti-coagulants provide options for reducing the risk of atrial fibrillation-related stroke. However, costeffectiveness comparisons with warfarin are warranted before observational health-economics study results can be applied clinically. Initiatives to remedy inequalities and improve access to care across Latin America should accompany risk factor modification and guideline-based prevention.